The digital conception of sigma - delta D/A converter implemented into FPGA - Kovar, Oldrich; Micek, Juraj (Communications - Scientific letters of the University of Zilina, 2000)
D/A converters are technical means which allow mutual communication between discrete and analog systems. Then base function is accurately comprehended in the statement “D/A converters create bridge between digital and analog world“. D/A converter transforms the discrete signal, progression of the binary numbers to the analog equivalent. Nowadays it is difficult to imagine realization of the digital control systems and some applications of the digital signal processing without using them. The authors of the article describe the digital conception of the Sigma - Delta D/Aconverter which is completely implemented into aprogrammable logical device FPGA, XC 4005E. The described conception of the Sigma -Delta D/A converter requires minimum of the external components, only one resistor and one capacitor as a lowpass filter.